Handbook of Clinical Psychology Competencies - Thomas, Jay C.; Hersen, Michel; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
In recent years there has been a tremendous growth in psychology as a field of study and in the number of students of clinical psychology in particular. The latter is partly due to the proliferation of professional schools of psychology that are devoted to practitioner-oriented degrees, rather than the traditional research-oriented course of study. Whatever school students emerge from, however, they are obliged to demonstrate proficiency in providing clinical services. This multi-volume handbook, is devoted to describing the core competency areas in providing psychological services which is relevant to practitioners as well as clinical researchers. As such, it covers assessment and conceptualization of cases, the application of evidence-based methods, supervision, consultation, cross-cultural factors, and ethics. The Handbook comprises three volumes with contributions by experts in each area. The goal is to provide detailed descriptions of competence levels and describe the developmental trajectory required to reach the highest of these levels. Each chapter in Volume I will follow a similar format including an overview, basic competencies, and expert competencies. This will facilitate easy comparison across chapters. All will be illustrated with case examples. Subsequent volumes will have a similarly structured format that will include maintenance factors, mechanisms of change, evidence-based treatment approaches, and a focus on the transition from basic skills to expert functioning. It is expected that the systematic presentation of skills will provide a gold standard against which to measure individual performance and in this regard will be valuable to students, instructors, and credentialing bodies.
General Competencies -- Basic Competencies -- Competencies in Adult Clinical Psychology -- Competencies in Child Clinical Psychology -- Ethical and Legal Issues -- Cultural Diversity -- Relationships -- Translating Science into Clinical Practice -- Diagnosis and Evaluation -- Clinical Interviewing with Adults -- Clinical Interviewing with Children -- Cognitive Assessment with Adults -- Cognitive Assessment with Children -- Behavioral Assessment with Adults -- Behavioral Assessment with Children -- Research -- Psychometrics -- Design and Analysis -- Single Subject Research -- Qualitative Research -- Epidemiology -- Literature Review and Meta Analysis -- Professional Roles -- Supervision -- Consultation -- Teaching -- Management and Administration -- Intervention and Treatment for Adults -- Adults -- Major Depressions -- Bipolar Disorder -- Simple Phobia -- Agoraphobia -- Obsessive Compulsive Disorder -- Post-Traumatic Stress Disorder -- Social Anxiety -- Schizophrenia -- Borderline Personality Disorder -- Substance Use Disorders -- Sexual Deviation -- Marital Dysfunction -- Physical Abuse -- Sexual Abuse -- Special Topics -- Geropsychology -- Pharmacological Adjuncts -- Intervention and Treatment for Children and Adolescents -- Major Depression -- Bipolar Disorder -- Anxiety Disorders -- Mental Retardation -- Pervasive Developmental Disorder -- Learning Disabilities -- Conduct Disorders and ODD -- Attention Deficit Hyperactivity Disorder -- Enuresis and Encopresis -- Tic and Habit Disorders -- Anorexia and Bulimia -- Substance Use Disorders -- Child Physical Abuse and Neglect -- Child Sexual Abuse -- Peer Problems -- Somatization Disorder -- Special Topics -- Pharmacological Adjuncts -- Family Issues.
Keywords: Philosophy (General).; Psychology, clinical; Psychology; Clinical Psychology